-15x+7y+15x-13y=

Simple and best practice solution for -15x+7y+15x-13y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15x+7y+15x-13y= equation:


Simplifying
-15x + 7y + 15x + -13y = 0

Reorder the terms:
-15x + 15x + 7y + -13y = 0

Combine like terms: -15x + 15x = 0
0 + 7y + -13y = 0
7y + -13y = 0

Combine like terms: 7y + -13y = -6y
-6y = 0

Solving
-6y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-6'.
y = 0

Simplifying
y = 0

See similar equations:

| 5s+2=6s-6 | | -17g-(-4)=-30 | | C=38.89+0.25x | | -19-(-19)-18= | | 5-4(3w-3)=-6 | | 8=3u+4u | | 8=60+4x | | -7+3f=4f+3 | | y/3-2=5/6 | | 0=x^3(4-x) | | 7w-3=6w-5 | | 7s+-5=9 | | 81=9x+x^2 | | 8.0a-6=-0.6a+22 | | 7x+7=6x-19 | | 5+3w+3-w= | | x^3-20=7 | | y/6-4=1 | | -5s=-9s-8 | | b-1.6//4=3 | | -19.3t-17.6=-17.1t | | x(12-2x)(10-2x)= | | -6(2x+3)=-30 | | -2+x^2=14 | | -12b+1+(13b-7)=0 | | 7/10-2=1 | | 67=5k-13 | | 8-3(p-4)=7 | | -x^2-14=5x | | (X-16)/42=0 | | (5+p)(5-8p)=0 | | x(x+1)+2=0 |

Equations solver categories